Evaluation and Its Impact of SARS-CoV-2 Inactivated Vaccine Candidate in K18-hACE2 Mice - A'la, Rofiqul; Rantam, Fedik Abdul; Wijaya, Andi Yasmin; Susilowati, Helen; Kuncorojakti, Suryo; Diyantoro, Diyantoro; Aswin, Ahmad; Rahmahani, Jola; Suwanti, Lucia Tri; Lukiswanto, Bambang Sektiari; Yudaniayanti, Ira Sari; Setiawan, Boedi (Universitas Airlangga, 2025)
The COVID-19 pandemic caused by SARS-CoV-2 requires effective vaccines to be developed. This study aimed to assess the impact of a SARS-CoV-2 inactivated vaccine candidate in k18-hACE2 mice by monitoring their body weight, immune activation, and inflammatory cytokines including IL-4, IL-6, TNF-α, and IFN-γ. The study utilized k18-hACE2 mice expressing the human angiotensin-converting enzyme 2 (hACE2) receptor. The mice were administered the inactivated vaccine candidate compared with sham and vehicle. Body weight was monitored, and serum samples were collected to measure IL-4, IL-6, TNF-α, and IFN-γ levels using ELISA. Data were evaluated using SPSS statistical analysis software. The administration of the SARS-CoV-2 inactivated vaccine candidate in k18-hACE2 mice did not result in significant changes in body weight compared to the control group. Furthermore, the levels of IL-4, IL-6, TNF-α, and IFN-γ were significantly reduced in the vaccinated mice compared to the control group, suggesting a dampening effect on the inflammatory response. This study demonstrates that the SARS-CoV-2 inactivated vaccine candidate has a minimal impact on the body weight of k18-hACE2 mice. Nevertheless, it successfully regulates the levels of IL-4, IL-6, TNF-α, and IFN-γ, suggesting its safety and beneficial impact. These findings contribute to understanding the vaccine's efficacy and safety profile in vaccine development.